Finite Element Analysis of Transhumeral and Transtibial Percutaneous Osseointegrated Endoprosthesis Implantation - Taylor, Carolyn E.; Henninger, Heath B.; Bachus, Kent N. (Frontiers in Rehabilitation Sciences, 2021)
Cadaveric mechanical testing of the Percutaneous Osseointegrated Docking System (PODS) for osseointegrated (OI) prosthetic limb attachment revealed that translation of the exact system from the humerus to the tibia may not be suitable. The PODS system, designed specifically for the humerus, achieved 1.4-4.8 times greater mechanical stability in the humerus than the tibia, despite morphology that indicated translational feasibility. To better understand this discrepancy, finite element analyses (FEA) modeled the implantation of PODS into the bones. Models from cadaveric humeri (n=3) and tibia (n=3) were constructed from CT scans, and virtual implantation preparation of an array of endoprosthesis sizes that made contact with the endosteal surface but did not penetrate the outer cortex. Final impaction of the endoprosthesis was simulated using a displacement ramp function to press the endoprosthesis model into the bone. Impaction force and maximum first principal (circumferential) stress were recorded to estimate stability to assess fracture risk of the system. We hypothesized that the humerus and tibia would have different optimal PODS sizing criteria that maximized impaction force and minimized first principal stress. The optimal sizing in the humerus corresponded to implantation instructions, whereas in the tibia optimal sizing occurred three sizes larger than the guidelines indicated. This FEA examination of the impaction force and the stress distribution leads us to believe that the same endoprosthesis strategy from the humerus is not suitable for the tibia because of thin medial and lateral cortices that compromise implantation.